Limited Usefulness of Capture Procedure and Capture Percentage for Evaluating Reproducibility in Psychological Science - Cheng, Yongtian; Li, Johnson Ching-Hong; Liu, Xiyao (Frontiers in Psychology, 2018)
In psychological science, there is an increasing concern regarding the reproducibility of scientific findings. For instance, Replication Project: Psychology (Open Science Collaboration, 2015) found that the proportion of successful replication in psychology was 41%. This proportion was calculated based on Cumming and Maillardet’s (2006) widely employed capture procedure (CPro) and capture percentage (CPer). Despite the popularity of CPro and CPer, we believe that using them may lead to an incorrect conclusion of (a) successful replication when the population effect sizes in the original and replicated studies are different; and (b) unsuccessful replication when the population effect sizes in the original and replicated studies are identical but their sample sizes are different. Our simulation results show that the performances of CPro and CPer become biased, such that researchers can easily make a wrong conclusion of successful/unsuccessful replication. Implications of these findings are considered in the conclusion.